2018
DOI: 10.1136/emermed-2018-207562
|View full text |Cite
|
Sign up to set email alerts
|

UK’s initial operational response and specialist operational response to CBRN and HazMat incidents: a primer on decontamination protocols for healthcare professionals

Abstract: The UK is currently in the process of implementing a modified response to chemical, biological, radiological and nuclear and hazardous material incidents that combines an initial operational response with a revision of the existing specialist operational response for ambulant casualties. The process is based on scientific evidence and focuses on the needs of casualties rather than the availability of specialist resources such as personal protective equipment, detection and monitoring instruments and bespoke sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…Dosing was therefore deemed considered reflective of a spray exposure and comparisons could subsequently be made between different decontamination protocols. Dry decontamination, LPS and technical decontamination, following current US emergency personnel guidance (4, 31), were then compared to the proposed improved procedures derived from in vitro hair and skin decontamination studies (10,32) and other human volunteer trials incorporating an initial dry decontamination step (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosing was therefore deemed considered reflective of a spray exposure and comparisons could subsequently be made between different decontamination protocols. Dry decontamination, LPS and technical decontamination, following current US emergency personnel guidance (4, 31), were then compared to the proposed improved procedures derived from in vitro hair and skin decontamination studies (10,32) and other human volunteer trials incorporating an initial dry decontamination step (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Dry decontamination (cleansing of the skin with dry absorbent materials) offers the opportunity to reduce the delay between casualty exposure and the onset of decontamination: previous in vitro and in vivo studies have demonstrated the value of dry decontamination in removing contaminants prior to the arrival and deployment of more formal decontamination measures (9-11). This has consequently been incorporated in the Initial Operational Response to mass casualty chemical exposure in the UK (12) and its operational and clinical value has been evaluated (13) as part of revised US federal guidance for emergency responders (4).…”
Section: Introductionmentioning
confidence: 99%
“…The intricacies of this response vary across the United States (Power et al , 2016). However, the overall response to mass casualty chemical incidents has been revised to incorporate disrobing (the removal of clothing), an improvised form of dry decontamination (DD) and specialist methods of decontamination (technical decontamination [TD]), similar to the principles being adopted in the United Kingdom (Chilcott et al , 2019a; UK Home Office, 2015).…”
mentioning
confidence: 99%
“…To date most studies have evaluated the removal of chemical simulants from the skin only. Outputs of these studies have been informative and have led to changes to both UK and US emergency decontamination protocols for chemical incidents 14,15 . However, few studies have examined the effectiveness of current decontamination interventions in removing chemicals from hair 7,[16][17][18][19][20] and even fewer have done so with human volunteers 10,14,21 .…”
mentioning
confidence: 99%